Anthelmintic efficacy of tinidazole against the progression of Toxocara canis larvae to the brain in mice - Minvielle, Marta Cecilia (1999)
The anthelmintic effect of tinidazole (100 mg/kg per day for 3 successive days) was tested in male Swiss CF-1 mice infected with second-stage Toxocara canis larvae at challenge doses of 250, 500, 1000, and 1500 embryonated eggs per mouse. The drug was given orally on days 3–5 postinfection (p.i.) to one-half of the animals, and all mice were killed on day 40 p.i. The number of larvae recovered from each mouse's brain and skeletal muscle was then scored in both groups. Tinidazole yielded a highly significant reduction in the total recovery of larvae from the test animals' brains at the second and third inoculum levels but no statistically significant reduction at the highest larval dose as compared with the values obtained in the untreated control animals.